2016
DOI: 10.1136/bjophthalmol-2016-308957
|View full text |Cite
|
Sign up to set email alerts
|

The use of Bruch's membrane opening-based optical coherence tomography of the optic nerve head for glaucoma detection in microdiscs

Abstract: In small optic discs, BMO-MRW and peripapillary RNFLT (OCT) have similar sensitivity to discriminate patients with glaucoma from normal controls; both exceed CSLT rim area in diagnostic power. In glaucomatous patients, BMO-MRW correlates strongest with visual field function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 28 publications
3
31
0
2
Order By: Relevance
“…Previous studies have shown the clinical utility of BMO-MRW parameters in diagnosing glaucoma, especially in cases of extreme optic-disc sample size, demonstrating better diagnostic capability than confocal scanning laser tomography and exhibiting a good structure function correlation [9,21]. In general, many studies have shown the SD-OCT BMO-MRW and pRNFL thickness parameters to surpass confocal scanning laser tomography as regards diagnostic capacity to detect glaucoma [3,5,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the clinical utility of BMO-MRW parameters in diagnosing glaucoma, especially in cases of extreme optic-disc sample size, demonstrating better diagnostic capability than confocal scanning laser tomography and exhibiting a good structure function correlation [9,21]. In general, many studies have shown the SD-OCT BMO-MRW and pRNFL thickness parameters to surpass confocal scanning laser tomography as regards diagnostic capacity to detect glaucoma [3,5,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated higher glaucoma diagnosis accuracy using BMO-MRW and a stronger association with functional parameters compared to conventional rim parameters [5][6][7]. Various authors have indicated the utility of BMO-MRW in diagnosing glaucoma in moderate myopic eyes [8] or small optic discs [9]. BMO-MRW also showed high intraday repeatability, similar to the RNFL thickness parameters, and independence from intraindividual intraocular pressure (IOP) changes [10].…”
Section: Introductionmentioning
confidence: 99%
“…In another study on 207 individuals, BMO‐MRA has also been shown to equalize differences in rim width between healthy small and large optic nerve heads (ONHs) and to have higher diagnostic power for glaucoma compared to conventional parameters (Enders et al. ,b,c).…”
Section: Introductionmentioning
confidence: 99%
“…Morphometric data for eyes with non‐glaucomatous macrodiscs has been published (Enders et al. ,b,c). Other less frequent ONH configurations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1,[4][5][6][7][8][9][10][11] Correlation of morphometric parameters of the ONH and visual field function has been evaluated in several studies. 1,[12][13][14][15][16][17][18][19][20][21][22] In addition to the clinically available parameters Bruch's membrane opening-based minimal rim width (BMO-MRW) and peripapillary retinal nerve fiber layer (RNFL) thickness, two studies on the two dimensional parameter Bruch's membrane opening minimal rim area (BMO-MRA) showed high diagnostic power for all ONH sizes and equalized differences in BMO-MRW between very large and very small ONHs. 1,23 As follow-up data become available, first studies were conducted to assess the performance of SD-OCT for detection of progression of glaucomatous damage to the ONH.…”
mentioning
confidence: 99%